'This is not the jungle, this is my barbecho': semantics of ethnoecological landscape categories in the Bolivian Amazon. (2nd January 2018) - Wartmann, Flurina M.; Purves, Ross S.
Abstract: Through a case study with Spanish-speaking Takana indigenous people in the Bolivian Amazon, we explored ethnoecological landscape categories, including their ecological underpinnings, cultural significance and hierarchical organisation. Using field walks and interviews with consultants, we elicited 156 ethnoecological landscape categories, 60 of which related to vegetation types. However, sorting exercises with landscape photographs revealed that vegetation was not a guiding organisation principle. Takana consultants organised ethnoecological landscape categories into geographical regions that contained different landscape features, including vegetation units, topographical or hydrological features. Comparing the documented ethnoecological landscape categorisation with a published scientific botanical classification of vegetation units, we observed some important conceptual differences, which in turn have implications for the management of such landscapes.